2017
DOI: 10.1074/jbc.m117.794099
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking of dicyclotyrosine by the cytochrome P450 enzyme CYP121 from Mycobacterium tuberculosis proceeds through a catalytic shunt pathway

Abstract: CYP121, the cytochrome P450 enzyme in that catalyzes a single intramolecular C-C cross-linking reaction in the biosynthesis of mycocyclosin, is crucial for the viability of this pathogen. This C-C coupling reaction represents an expansion of the activities carried out by P450 enzymes distinct from oxygen insertion. Although the traditional mechanism for P450 enzymes has been well studied, it is unclear whether CYP121 follows the general P450 mechanism or uses a different catalytic strategy for generating an ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
109
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(121 citation statements)
references
References 61 publications
12
109
0
Order By: Relevance
“…In our recent study, we found that peracetic acid can oxidize the CYP121-cYY complex via a peroxide shunt mechanism, in which we observed the rapid formation of a probable ferric alkyl-peroxo species. 15 In the later steps of the reactions it catalyzes, CYP121 functions more like a peroxidase than a typical P450. 15 We noticed that, from the very first reaction step, CYP121 does not follow the general P450 chemical mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our recent study, we found that peracetic acid can oxidize the CYP121-cYY complex via a peroxide shunt mechanism, in which we observed the rapid formation of a probable ferric alkyl-peroxo species. 15 In the later steps of the reactions it catalyzes, CYP121 functions more like a peroxidase than a typical P450. 15 We noticed that, from the very first reaction step, CYP121 does not follow the general P450 chemical mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…15 In the later steps of the reactions it catalyzes, CYP121 functions more like a peroxidase than a typical P450. 15 We noticed that, from the very first reaction step, CYP121 does not follow the general P450 chemical mechanism. In the generally accepted mechanism of P450 enzymes, binding of the primary organic substrate results in release of the axial water ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…287 Given the essential nature of CYP121 to the survival of M. tuberculosis, 288 this P450 has been extensively characterised by a number of groups, which have afforded structural, biochemical and mechanistic insights into the function of this P450. [289][290][291] Mechanistically, the formation of the C-C bond (similar to aviolin) has been postulated to occur either by via proton coupled electron transfer or electron tunnelling between the two aromatic rings, 177,292 which is a needed to avoid having to completely re-orient the substrate within the active site during catalysis, which was an early mechanistic postulate in this case. 287 One of the more impressive series of transformations reported to occur during bacterial DKP synthesis is found in the biosynthesis of bicyclomycin.…”
mentioning
confidence: 99%
“…From a mechanistic perspective, the crosslinking reaction likely occurs by hydrogen abstraction from the ring closest to the heme iron, with subsequent generation of a radical species in the distal aviolin occurring either via proton coupled electron transfer or electron tunnelling as has been postulated for the crosslinking reaction performed by CYP121 (vide infra). 177 A further interesting note in the investigation of CYP158 enzymes has been their use in mechanistic studies, where the Green group has been able to use these enzymes to investigate the highly reactive intermediates that are found within the P450 active cycle. …”
mentioning
confidence: 99%